The Effect of Soft Skill, Motivation and Job Satisfaction on Employee Performance through Organizational Commitment - Saihu Akla; Rhian Indradewa (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to examine the effect of soft skills, motivation, job satisfaction on employee performance through organizational commitment. The test is carried out by testing the main influence of soft skills, motivation and job satisfaction on organizational commitment and continued by testing soft skills, motivation, job satisfaction, organizational commitment to employee performance. The population in this research is the marketing employees of Bank Mandiri in Regional Office 4. The method of this research is by distributing questionnaires to 400 respondents and then testing for Normality and SEM - Path in lisrel. The results showed that Soft Skills, Motivation and Work Goals on Employee Performance through Organizational Commitment all variables had a significant effect.